Dance of the money bees : a professional speaks frankly on investing - Train, John. (New York : Harper & Row, 1974)
Survival is a competition. What you have, including your savings, others want, and will struggle to get. The push to take it back from you is as relentless as that of the sea to overcome the dikes that contain it or the jungle to enfold a patch of cleared ground. The whole order of nature pushes to reclaim its own. Governments bow to that kind of pressure. Pieces of paper are a weak defence. Only through deep understanding and superior tactics can the investor hope to preserve even part of what he has earned, and it gets harder every year...
Includes index.
obn 24/01/2019
Loans
Keywords: Investments; Stockbrokers